HIV-1 acquired drug resistance to integrase inhibitors in a cohort of antiretroviral therapy multi-experienced Mexican patients failing to raltegravir: a cross-sectional study - Orta-Resendiz, Aurelio; Rodriguez-Diaz, Roberto A.; Angulo-Medina, Luis A.; Hernandez-Flores, Mario; Soto-Ramirez, Luis E. (AIDS research and therapy, 2020)
Background In resource-limited settings, multi-experienced HIV infected patients are often prescribed raltegravir for salvage therapy. Patients failing raltegravir-containing regimens require other drugs including other integrase inhibitors. In this context, real-life data about the resistance and cross-resistance pathways between integrase inhibitors is limited. The aim of this study was to investigate integrase resistance pathways in a cohort of Mexican multi-experienced patients failing of a raltegravir-containing salvage regimen. Methods Twenty-five plasma samples from subjects failing antiretroviral regimens which included raltegravir were obtained from various healthcare centres from 2009 to 2017 in Mexico. Antiretroviral history and demographics were collected. Samples were processed for integrase resistance genotyping testing by sequencing. The viral sequences were analysed with the Stanford HIV drug resistance database algorithm. Data was analysed with SPSS Statistics software. Results We found a mean viral load of 4.17 log 10 c/mL (SD 1.11) at the time of virologic failure. Forty-eight percent of the samples were raltegravir resistant. The Y143R/H/C substitutions were the most prevalent, followed by the N155H, and both Q148H/K and G140S/A in the same proportion. The Q148 + G140 combination was found in (12%) of the samples. Cross-resistance to elvitegravir was found in 83.3% and in 18.2% for both dolutegravir and bictegravir. Thirteen samples (52%) were susceptible to the four integrase strand-transfer inhibitors. Conclusions Our findings suggest a high occurrence of resistance and cross-resistance to other integrase inhibitors among multi-experienced subjects failing raltegravir. We found a modestly lower proportion of cross-resistance to dolutegravir than data from clinical trials. Likely this drug could be used for salvage therapy. Explanations for the absence of mutations in half of the samples, other than reduced adherence, should be further investigated. Close surveillance is needed.